PENGARUH TRAINING NEEDS ANALYSIS DAN PARTISIPASI SUBJECT MATTER EXPERT TERHADAP PENGEMBANGAN KONTEN PEMBELAJARAN INTERNAL PADA PRAKTISI LEARNING & DEVELOPMENT DI JABODETABEK - Caiseria, Riska; Saragi Sitio, Vera Sylvia (Jurnal Inovatif Mahasiswa Manajemen, 2025)
This study is motivated by the importance of identifying training needs and the role of Subject Matter Experts (SMEs) in ensuring that training materials remain relevant to required competencies. The objective is to analyze the influence of Training Needs Analysis (TNA) and SME participation on the development of internal learning content among Learning & Development (L&D) practitioners in the Greater Jakarta (Jabodetabek) area. The study employs a quantitative associative approach with a sample of 50 L&D practitioners from various industry sectors. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression after instrument feasibility testing. The findings indicate that, partially, TNA has a significant effect on the development of internal learning content, while SME participation does not show a significant effect. However, simultaneously, both variables exert a significant influence, contributing 14.3%, while the remaining 85.7% is explained by external factors beyond the scope of this study. These results suggest that the development of internal learning content is not solely determined by TNA and SME participation, but also by other external factors outside the proposed model.